Histopathological Profile of Childhood Thyroid Carcinoma in Ibadan, Southwestern Nigeria (2020)
Background Thyroid carcinoma is a common endocrine malignancy. It is, however, rare in childhood and often occurs as a result of radiation exposure or inherited genetic mutations. Most childhood thyroid carcinomas are well differentiated. There are very few epidemiological studies of this disease in Nigeria, and our study aimed to determine the frequency in a subset of our population. The study aimed to determine the prevalence and histopathological characteristics of childhood thyroid carcinoma in our environment. Methods This was a retrospective review of histopathologically diagnosed thyroid carcinoma in children less than 18 years of age in the Department of Pathology, University College Hospital, Ibadan, over a 40-year period. Histopathological diagnosis, age, sex, and other relevant clinical information were extracted from the hospital records and surgical pathology records of the department. All cases of patients under 18 years old had their slides re-examined and reclassified by two pathologists according to the World Health Organization histopathological classification of thyroid tumours. Results There were 25 cases of thyroid carcinomas seen in children within the study period. Papillary thyroid carcinoma was the most common, accounting for 80% of the cases. Follicular carcinoma accounted for 12%, and medullary and anaplastic carcinoma accounted for 4% each. The mean age at presentation was 13 years. There was a female preponderance, with females accounting for 60% of cases. Tumours with distant metastasis made up 20% of the cases. Conclusion Childhood thyroid carcinomas are rare in our environment, with a minority of cases presenting with metastases.